TECHNOLOGIES FOR DEVELOPING THE CREATIVE POTENTIAL OF FUTURE VOCATIONAL TRAINING TEACHERS - Kovalchuk, Vasyl; Vovk, Lyudmyla; Volkova, Natalііa; Vovk, Bohdan; Horbatiuk, Roman (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The article examines the important aspect of training future teachers of professional education, namely applying technologies to stimulate and develop their creative potential. The formation and development of the creative potential of an individual is of great importance in the context of the educational process and the formation of the future teacher, since modern society has set high demands on specialists regarding their professional qualities. Applying the technologies for developing student’s creativity is a key element of the modern educational process aimed at stimulating creative thinking and personal development of the future specialist. The article explores current challenges associated with preparing future professional education educators for the implementation of educational technologies that stimulate the unfolding of learners' creative potential. The materials of this study focus on the issue of technologizing the educational process in higher education institutions, which will contribute to its qualitative improvement, wider adoption of innovative approaches, modern development tools, teaching methods, and forms that will ensure the development of learners' creative abilities. The concept of pedagogical technology is examined, its essence and classification are revealed, and aspects of implementing a technological approach in the educational process of preparing future professional education educators are highlighted. The results of the experimental research presented in the article emphasize the importance of using modern pedagogical technologies and draw attention to the need to search for rational ways of teaching, develop modern principles, and justify the specifics of their implementation that meet the requirements for education aimed at shaping and developing the creative personality of the future professional. The article highlights the practical experience of implementing educational technologies in the institutions of higher education and defines the effective methods of evaluating and supporting the creative potential of students. The key aspects that contribute to the improvement of the professional development of future specialists and the creation of conditions for their creative self-expression in the educational process and the further professional activities were considered.